Evaluation of the efficiency of maize ecotypes in different localities and times in the Ancash region, Peru - Huaytalla-Torres, Gelar Isaias (2017)
The objective of the present investigation is to evaluate the yield of the maize crop against the current climatic variability. In this sense, plots were installed in each locality at the beginning of each agricultural season (October, November and December), with two densities, one at commercial density 80 x 60 cm and three plants per plot and at a low density of sowing per hybrid 3 Plants / m2, with an experimental area per plot (furrows, 4 for each density) in order to have the necessary material for the sampling to be carried out during the crop cycle; Evaluations, observations and measurements were made on the two central rows. The plots were irrigated and fertilized so that there was no water or nutritional deficiency.The ecotypes studied were Huaraz, Yungay, Chingas and Marcará, with the result that the ecotypes with the highest yield (kgrs) were, in the town of Canyasbamba, the ecotypes Huaraz, Chingas and Marcará, in the locality of Huaraz the ecotype Chingas and in the locality of Tingua the best behavior was generated by the ecotype Marcará.